THE EFFECT OF MOTIVATION AND COMPENSATION TOWARD JOB SATISFACTION IN PT. SIG ASIA BITUNG - Bawoleh, Vergina Sheren; Pangemanan, Sifrid S.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2015)
Employees are important assets to reach organizational goals and employee job satisfaction is very important. To attain job satisfaction, employee must be motivated in doing their jobs first. Lack of motivation can also lead to high job turnover in the company and will increase the cost of training and hiring new employees. Besides motivation, job satisfaction of employees is also influenced by compensation. The objective of this research is to know the significant effect of motivation and compensation on job satisfaction simultaneously, partially. This research uses quantitative method and the Multiple Regression Analysis. The population observed is the employees of PT. SIG Asia with 30 respondents as the sample size and simple random as sampling method was used. The result of this research is there is significant effect of motivation and compensation on job satisfaction partially and simultaneously. The management of this company is expected to keep paying attention to motivation and compensation that could encourage employees to increase their performance. Keywords: job satisfaction, motivation and compensation.